2017
DOI: 10.1523/jneurosci.3352-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Early Golgi Abnormalities and Neurodegeneration upon Loss of Presynaptic Proteins Munc18-1, Syntaxin-1, or SNAP-25

Abstract: The loss of presynaptic proteins Munc18-1, syntaxin-1, or SNAP-25 is known to produce cell death, but the underlying features have not been compared experimentally. Here, we investigated these features in cultured mouse CNS and DRG neurons. Side-by-side comparisons confirmed massive cell death, before synaptogenesis, within 1-4 DIV upon loss of t-SNAREs (syntaxin-1, SNAP-25) or Munc18-1, but not v-SNAREs (synaptobrevins/VAMP1/2/3 using tetanus neurotoxin (TeNT), also in TI-VAMP/VAMP7 knock-out (KO) neurons). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 68 publications
4
74
0
Order By: Relevance
“…In these initial experiments, we used microdot cultures, where single neurons grow on islands of rat astrocytes. This reduced and standardized preparation allows quantitative comparisons between neurons expressing different variants for many morphological and functional parameters ( Wierda et al , 2007 ; Schmitz et al , 2011 ; Santos et al , 2017 ). Subsequently, we tested a selection of these variants in neurons carrying a single copy of the Stxbp1 gene to model the situation in patients (see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these initial experiments, we used microdot cultures, where single neurons grow on islands of rat astrocytes. This reduced and standardized preparation allows quantitative comparisons between neurons expressing different variants for many morphological and functional parameters ( Wierda et al , 2007 ; Schmitz et al , 2011 ; Santos et al , 2017 ). Subsequently, we tested a selection of these variants in neurons carrying a single copy of the Stxbp1 gene to model the situation in patients (see below).…”
Section: Resultsmentioning
confidence: 99%
“…The most firmly established molecular function of Munc18-1 is to prepare synaptic vesicles for release in the presynaptic nerve terminal (reviewed in Toonen and Verhage, 2007 ). Consequently, in the absence of Munc18-1, neurons have no synaptic activity, not even spontaneous activity ( Verhage et al , 2000 ) and die within a few days in vitro and in vivo ( Verhage et al , 2000 ; Heeroma et al , 2004 ; Santos et al , 2017 ). Expression of five human variants in Stxbp1 null mutant neurons rescued neuronal viability: C180Y, M433R, G544D, T574P and C522R ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most reports that involve GA in cell death signaling are dealing with neurodegenerative diseases (Passemard et al , ). For example, cultured neurons from the central nervous system or dorsal root ganglia degenerate while manifesting early cis ‐GA abnormalities upon depletion of proteins involved in synaptic transmission (syntaxin‐1, Munc18‐1, SNAP‐25) (Santos et al , ). Similarly, specific removal of GA‐relevant proteins can precipitate neurodegeneration in mice (Liu et al , ) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, since it has been reported that Munc18–1 controls aggregative propensity of α-synuclein and that C180Y mutation induces abnormal aggregation of α-synuclein, the migration defects observed in this study might be attributable to the level of toxic α-synuclein aggregation [ 17 ]. In this context, disrupted function of Munc18–1 has been shown to trigger neuronal degeneration [ 53 , 54 ]. Given that clinical symptoms are different in respective patients with MUNC18–1 gene abnormalities, additional environmental or genetic factors affecting neurodegeneration are suggested in each patient.…”
Section: Discussionmentioning
confidence: 99%